2017
DOI: 10.1080/02786826.2017.1292346
|View full text |Cite
|
Sign up to set email alerts
|

Effective density and volatility of particles sampled from a helicopter gas turbine engine

Abstract: The effective density and size-resolved volatility of particles emitted from a Rolls-Royce Gnome helicopter turboshaft engine are measured at two engine speed settings (13,000 and 22,000 RPM). The effective density of denuded and undenuded particles were measured. The denuded effective densities are similar to the effective densities of particles from a gas turbine with a ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2 double annular combustor as well as a wide variety of internal combustion engines. The denuded eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Figure 3 summarizes effective density measurements from many authors for several source categories, only considering fresh soot where volatile material was removed (via thermal or catalytic denuding) or in some circumstances where the amount of volatile material was relatively low. Results are shown for: compression ignition engines fueled with diesel or natural gas (Fujitani et al 2016;Graves et al 2015;Leung et al 2017;Maricq and Xu 2004;Olfert, Symonds, and Collings 2007;Rissler et al 2013); spark ignition engines fueled with gasoline or ethanol blends (Dastanpour et al 2016;Graves, Koch, and Olfert 2017;Momenimovahed and Olfert 2015); gas turbines (Johnson et al 2015;Olfert et al 2017); and a wide range of premixed and non-premixed burners (Dickau et al 2016;Ghazi et al 2013;Kazemimanesh et al 2019;Pagels et al 2009;Rissler et al 2013). Results from individual studies that went into the Figure 3 summaries are shown in the SI.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 summarizes effective density measurements from many authors for several source categories, only considering fresh soot where volatile material was removed (via thermal or catalytic denuding) or in some circumstances where the amount of volatile material was relatively low. Results are shown for: compression ignition engines fueled with diesel or natural gas (Fujitani et al 2016;Graves et al 2015;Leung et al 2017;Maricq and Xu 2004;Olfert, Symonds, and Collings 2007;Rissler et al 2013); spark ignition engines fueled with gasoline or ethanol blends (Dastanpour et al 2016;Graves, Koch, and Olfert 2017;Momenimovahed and Olfert 2015); gas turbines (Johnson et al 2015;Olfert et al 2017); and a wide range of premixed and non-premixed burners (Dickau et al 2016;Ghazi et al 2013;Kazemimanesh et al 2019;Pagels et al 2009;Rissler et al 2013). Results from individual studies that went into the Figure 3 summaries are shown in the SI.…”
Section: Methodsmentioning
confidence: 99%
“…Even though the aforementioned VPR methods were originally designed for motor vehicle exhaust sampling, they have since extended in other applications such as marine or aircraft (Olfert et al 2017) exhaust PM measurements, where volatile species concentration and composition may be substantially different. In particular, for marine exhaust, semi-volatile species concentrations may be substantially higher than modern motor vehicle exhaust, owing to the high sulfur content (FSC) of marine fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the DMA-particle mass analyzer system is very popular in determining the q eff of engine exhaust particles (Olfert et al 2017;Park, Kittelson, and McMurry 2004;Maricq and Xu 2004;Sakurai et al 2003;Park et al 2003a) and ambient aerosols (Wu et al 2019;Qiao et al 2018;Rissler et al 2014), the q eff measurement of primary aerosol emitted from BB are still limited (Sumlin et al 2018;Zhai et al 2017;Li et al 2015). Most of the studies that determined aerosol mass from the particle size distribution applied an assumed density ranging from 1.0 g cm À3 to 1.7 g cm À3 regardless of the diameter, aging conditions, and morphology of the particles (Corbin et al 2019;Kumar et al 2018;Gkatzelis et al 2016;Saliba et al 2016;Vakkari et al 2014;Flowers et al 2010).…”
Section: Introductionmentioning
confidence: 99%